A MILP-based modular energy management system for urban multi-energy systems: Performance and sensitivity analysis. (1st March 2020) - Moser, A.; Muschick, D.; Gölles, M.; Nageler, P.; Schranzhofer, H.; Mach, T.; Ribas Tugores, C.; Leusbrock, I.; Stark, S.; Lackner, F.; Hofer, A.
Highlights: Novel modular modeling approach for an energy management system for urban multi-energy systems. Modeling of complex multi-energy system configurations. Approximate consideration of non-linear and hybrid system behavior using mixed logical dynamical (MLD) system models. Performance and sensitivity analysis of a MILP-based energy management system. Abstract: The continuous increase of (volatile) renewable energy production and the coupling of different energy sectors such as heating, cooling and electricity have significantly increased the complexity of urban energy systems. Such multi-energy systems (MES) can be operated more efficiently with the aid of optimization-based energy management systems (EMS). However, most existing EMS are tailor-made for one specific system or class of systems, i.e. are not generally applicable. Furthermore, only limited information on the actual savings potential of the usage of an EMS under realistic conditions is available. Therefore, this paper presents a novel modular modeling approach for an EMS for urban MES, which also enables the modeling of complex system configurations. To assess the actual savings potential of the proposed EMS, a comprehensive case study was carried out. In the course of this the influence of different user behavior, changing climatic conditions and forecast errors on the savings potential was analyzed by comparing it with a conventional control strategy. The results showed that using the proposed EMS in conjunction with supplementary system components (thermal energy storage and battery) an annual cost savings potential of between 3 and 6% could be achieved.